Persepsi dan Pengetahuan Pelaku UMKM Desa Rantau Rasau II dalam Bertransaksi di Bank Syariah Indonesia - Andre Maulana; Haeran Haeran; Kuswanto Kuswanto; Alisyah Pitri Pitri; Ahmad Edi Saputra; Erwina Kartika Devi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the perceptions and level of knowledge of Micro, Small, and Medium Enterprises (MSMEs) in Rantau Rasau II Village regarding Islamic banking services, particularly in conducting transactions at Bank Syariah Indonesia (BSI). The background of this study is based on the importance of Islamic financial literacy among MSMEs to support economic growth based on Islamic principles. The method used in this study is descriptive quantitative with data collection through questionnaires distributed to MSMEs in the village. The results show that most MSMEs have limited basic knowledge regarding Islamic banking principles and products. Nevertheless, perceptions of Bank Syariah Indonesia are generally quite positive, especially related to aspects of halal transactions and fairness of the profit-sharing system. Factors such as education level, business experience, and access to information are variables that influence the level of knowledge and perceptions of MSMEs. These findings imply the need for more intensive education and socialization regarding Islamic banking so that MSMEs can have more trust and actively utilize BSI services optimally.